Analysis of microsatellite aberrations and loss of heterozygosity in follicular lymphoma, diffuse large B-cell lymphoma, and high-grade B-cell lymphoma patients - K. A. Sychevskaya; A. E. Misyurina; E. E. Nikulina; N. V. Risinskaya; R. R. Abdurashidova; Z. T. Sarakaeva; A. U. Magomedova; A. B. Sudarikov; S. K. Kravchenko (Онкогематология)
Background. The study of genetic predictors of non-Hodgkin’s lymphomas prognosis is one of the most relevant areas of oncohematology. It is extremely interesting to search for integral markers that reflect the most important stages of tumor pathogenesis. DNA repair system plays one of the key roles in genomic instability. Aberrations of microsatellite repeats such as microsatellite instability (MSI), in particular elevated microsatellite alterations at selected tetranucleotide repeats (EMAST) is characteristic for mismatch repair system and loss of heterozygosity (LOH) is an integral feature of genomic instability.Objective. Analysis of MSI, EMAST, LOH significance in follicular lymphoma (FL), diffuse large B-cell lymphoma (DLBCL), and high-grade B-cell lymphoma (HGBL) patients.Materials and methods. The study was performed by multiplex PCR and fragment analysis with diagnostic panels COrDIS Plus and COrDIS MSI in 85 FL patients, 32 DLBCL patients, and 37 HGBL patients.Results. The frequency of LOH in the general FL group was 40/81 (49.4 %), MSI – 10/82 (12.2 %), EMAST – 15/81 (18.5 %). The frequency of LOH in the HGBL group was 21/31 (67.8 %), MSI – 11/37 (29.7 %), EMAST – 13/31 (41.9 %). The frequency of LOH in the DLBCL group was 18/29 (62.0 %), MSI – 5/32 (15.6 %), EMAST – 14/32 (43.8 %). When considering the morphological types of FL, it was noted that a higher frequency of genetic aberrations was characteristic of lymphomas with a more aggressive morphology (p <0.05). LOH identifies FL and HGBL patients with an unfavorable prognosis. The EMAST analysis allows identifying additional patients in the LOH+ cohort with early events and low EFS.Conclusion. LOH and EMAST have a prognostic value for FL and HGBL. No associations of LOH and EMAST with the survival were observed in DLBCL. Changes in mononucleotide repeats in FL, DLBCL and HGBL did not correspond to the MSI-H characteristic of solid tumors. For this reason, the clinical consequences of MSI-H in solid neoplasms, in particular the efficacy of immune checkpoint inhibitors, in lymphomas cannot be expected to be replicated solely on the basis of microsatellite aberrations detection.